2018
DOI: 10.31925/farmacia.2018.6.19
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Docking, and Antibacterial Activity Evaluation of Some Novel Norfloxacin Analogues

Abstract: A novel series of 7 or 3-substituted norfloxacin derivatives were synthesized and characterized by 1 H NMR, MS and elemental analysis techniques. All the synthesized compounds were evaluated for antimicrobial activity against both Gram-positive and Gram-negative bacteria and the MIC and MBC values were calculated by the broth dilution method. To understand the influence of the different type of substituents on the pharmacokinetic properties and the interaction with the target enzyme of fluoroquinolones (DNA gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…These results seem to correlate with those reported by other research endeavors that signalized the problematic outcome of the initiative of increasing C7 fluoroquinolone substituent’s size [6,12,13,14,21]. Improved biological activity can be obtain if a new molecular binding mode is achieved for the quinolone-topoisomerase-DNA ternary complex [3,9,11].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These results seem to correlate with those reported by other research endeavors that signalized the problematic outcome of the initiative of increasing C7 fluoroquinolone substituent’s size [6,12,13,14,21]. Improved biological activity can be obtain if a new molecular binding mode is achieved for the quinolone-topoisomerase-DNA ternary complex [3,9,11].…”
Section: Resultssupporting
confidence: 84%
“…This new drug class is known as the quinoxolidinones and contains many promising molecules, including MCB3837 and MCB3681 [20]. In this context, our previous efforts [21] represent the first known report of a thiazolidinedione-fluoroquinolone hybridization and as such, we set out to obtain new norfloxacin derivatives that include a thiazolidinedione substituent at the piperazin-4-yl moiety. The key rationale behind choosing thiazolidinedione was the versatility of this nucleus, that is present in many antimicrobial and anti-biofilm molecules [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Through the displacement of EB molecules fixed in the DNA structure and their replacement with the studied indole derivatives, we observe a decrease in the intensity of the fluorescent signal issued by the DNA-EB system, along with the increase of the indole concentration added in the system. The scientific literature states that a compound interacts through intercalation with the double-stranded DNA structure, if it is registered a decrease over 40% of the fluorescent signal issued by the DNA-EB system [20,22,32]. Table II shows the obtained fluorescence intensities following the addition of increasing concentrations of indoles, depicted by the resulting indole/DNA molar ratio.…”
Section: Fluorometric Ethidium Bromide Intercalating Studies For Depicting the Dna-indole Interactionsmentioning
confidence: 99%
“…Nevertheless, DNA interaction with several compounds fixed at the level of specific sites of the DNA structure is the starting point of some processes inducing the reversible or irreversible degradation of nucleic acids. Therefore, the study of the interaction between drugs or endogen key molecules and DNA plays a key role in elucidating biochemical mechanisms of action and it is of great significance for the synthesis of new therapeutic molecules targeted to DNA [1,15,[20][21][22][23][28][29][30]. In cancer therapy, small molecules are synthesized for binding to various parts of DNA by groove binding, via intercalation, cross-linking or even DNA strandscission [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Literature revealed that clubbed 1,2,4‐triazolyl‐1,3,4‐oxadiazole and 1,3,4‐triazolyl‐thiazoles are new classes of azole antimycobacterials, which are proven to be highly active both in vitro and in vivo . Many researchers have synthesized 1,3,4‐oxadiazole derivatives and screened, for biological activity , 2‐(4‐isopropylthiazol‐2‐yl)‐5‐aryl‐1,3,4‐oxadiazoles , 2,3‐dihydrothiazoline‐substituted 1,3,4‐oxadiazole , 1,2,4‐triazolo[1,5‐a]pyrimidine‐substituted 1,3,4‐oxadiazoles , and 5‐dithiazolyl‐2‐R‐1,3,4‐∆4‐oxadiazoline derivatives, which showed antimicrobial, antitumor, and antifungal activities. These results prompted us to design new thiazolyl‐1,3,4‐oxadiazole derivatives and screen for antifungal activity.…”
Section: Introductionmentioning
confidence: 99%